The Future of Audit Keeping Capital Markets Efficient - Houghton, Keith (ANU Press, 2010)
At a time when increased independence requirements for auditors, legal backing for auditing standards, and increased audit documentation requirements have occurred, this book examines key issues in the market for audit services in Australia. It investigates issues including: the understandability of audit and the state of the audit expectations gap; auditors' business acumen and industry expertise; the auditors' use of materiality; whether or not the increasingly prescriptive nature of auditing is creating a distraction from the 'real' audit task and stifling auditors' judgement; whether or not CLERP 9 reforms involving audit partner rotation and restrictions on non-audit service provision are efficient and effective and reactions to the increasing scrutiny of auditors and audit firms by regulators. With its thorough coverage of contemporary issues, this book intersperses the authors' summaries, interpretations and recommendations with the perceptions, expressed in their own words in order to faithfully convey their candid assessments, of users of audit reports, purchasers and suppliers of the audit product, auditing standard setters and regulators of the audit market.